Examination of pain relief effect of Goreisan for glossodynia. Issue 33 (14th August 2020) - Ayuse, Takao; Okayasu, Ichiro; Tachi-Yoshida, Mizuki; Sato, Jun; Saisu, Hironori; Shimada, Masahiko; Yamazaki, Yoko; Imura, Hiroko; Hosogaya, Naoki; Nakashima, Sawako
Abstract: Background: Pain in glossodynia may be severe; it may prevent patients from working, interfere with daily life activities, and necessitate a patient's visit to a medical institution for consultation and treatment. The pain may be described as persistent and burning (tingling, tingling) or stinging. Patients may complain of dry mouth (dryness), which is thought to cause inflammation of the tongue and gingival mucous membranes and increased pain. Medications are prescribed based on the symptoms of glossodynia, and the therapeutic effect is confirmed. However, each drug has side effects, for example, pain may reduce, but drowsiness and dizziness may occur; further, there is always a tendency of drowsiness. On the other hand, Goreisan, a Chinese herbal medicine, has already been used by physicians to treat pain in the oral and maxillofacial regions resulting from rapid changes in air pressure. However, the lack of high-quality clinical research has been of concern, and a randomized clinical trial to investigate the efficacy and safety of Goreisan for treatment of pain in glossodynia is warranted. Methods/design: This multicenter, randomized, controlled study will involve patients treated for glossodynia-related pain. In the experimental group, Goreisan will be taken for 12 weeks in combination with conventional treatment. Participants in the control group will not take any Kampo medicine; only the standard treatment will be taken. Subsequently, the degree of pain will be assessed, and saliva tests of all the patients on their first visit will be performed. Goreisan will be taken at a dose of 7.5 g/d (minute 3) for 12 consecutive weeks. Twelve weeks later, the degree of pain of each patient will be assessed. Discussion: The purpose of this study is to investigate the efficacy of Goreisan for pain reduction in patients undergoing treatment for glossodynia-related pain. If pain in glossodynia patients can be reduced by the administration of Goreisan, its candidacy as an alternative treatment for pain in glossodynia can be further supported by more reliable research. Trial registration: The study was registered in the jRCTs071200017. URL https://jrct.niph.go.jp/latest-detail/jRCTs071200017 . Abstract : Supplemental Digital Content is available in the text